The method for evaluation of efficiency of the concept of centrally managed distribution in cities - Wasiak, Mariusz; Jacyna, Marianna; Lewczuk, Konrad; Szczepański, Emilian (Transport, 2017)
The paper describes proecological solution dedicated for organizing logistics services in urban areas. Proposed solution is based on cross-docking processes combined with consolidation centres. Authors proposed new method of estimating economic and social benefits from implementing centrally managed cooperation of logistics operators using common city consolidation hubs. Developed mathematical model bases on Vehicle Routing Problem (VRP) with vehicles of different types, limited loading capacities and multiply depots characterized by limited throughput. Proposed approach was supported by case study of integration of distribution processes in Warsaw (Poland) performed by three medium-size logistics operators. The central management of distribution was investigated in variants assuming using existing warehouses and with new configuration of logistics network developed with using SIMMAG 3D tools. As it was proved for analysed case, total costs of distribution in the city after implementation of centrally managed distribution were reduced by 8.1% for variant with current depots and by 26.5% for variant with new logistics network, while emission of carbon monoxide (CO) was reduced respectively by 7.8 and 16.7%.